Regimes de crescimento e regimes de políticas públicas: Uma revis\~ao da literatura e alguns resultados preliminares - Claudio Roberto Amitrano; Luís Carlos Garcia de Magalh\~aes; Lucas Ferraz Vasconcelos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The main aim of the paper is to analyze the evolution of growth regimes in a selected set of Latin American countries between 2000 and 2021, in order to characterize them in relation to their demand regimes growth, such as export-led, investment-led or consumption-led. Additionally, supply-side determinants are considered, which allow identifying the productivity regimes that are associated with these growth regimes. The paper seeks to contribute to identifying and evaluating the causes of the low economic performance, in general, of Latin American countries and, in particular, of Brazil since the 1980s. Several factors have been identified as causes of this delay, including institutions, productive structure and demand regimes. A review of the economic literature on the topic and the preliminary empirical results obtained are presented, in order to contribute to identifying the driving factors and obstacles to economic growth in the selected Latin American countries, including Brazil.
Keywords: E12; O11; O40; O54; 330; Latin America; economic growth; demand regime; productivity regime